CONOCIMIENTO Y APLICACIÓN DEL PROCESO DE ENFERMERÍA - Céspedes J., Marta Luz; Jaramillo U., Doralba; Pulido de L., Socorro; Ruiz M., Yolanda; Uribe E., Maria Teresa; Gutierrez, Maria Eugenia (Investigación y Educación en Enfermería, 2014)
.